Estudio de la fecundidad de Insulaspis gloverii (Homoptera: Diaspididae) - Gonzalez, C.=700 1 Rodriguez, J.L.
(Es, En)
Ilus., 6 ref.
Keywords: INSULASPIS; HOMOPTERA; DIASPIDIDAE; INSECTA; FECUNDIDAD; PLANTACION; CITRUS SINENSIS; CUBA; INSULASPIS GLOVERIL; CIENCIA Y TECNICA EN LA AGRICULTURA: CITRICOS Y OTROS FRUTALES